Elementy diachroniczne w synchronicznym opisie estońskiej fleksji nominalnej - Bielecki, Robert (Investigationes Linguisticae, 2009)
The present paper aims to demonstrate the synchronic inadequacy for the description of modern Estonian nominal flexion of such notions as: (i) lõpumuutus, lõpuvaheldus ‘alternation of final sound(s) (of the stem of a word)’, and (ii) astmevaheldus ‘gradation’ in the shape proposed by Estonian linguistis. The first seems to be founded only on diachronic relations resulting from the vanishing of final sound(s) of the stem of the historical Nom Sg and historical endings of Gen Sg (*-n), Acc Sg (*‑m) and partially Part Sg (*-ta, *-tä). According to the approach discussed in the present paper, this notion is not relevant to contemporary Estonian. Its existence in Estonian linguistics interferes with the recognition of new endings of Gen Sg, (Acc Sg) and partially Part Sg, which seem to have originated because of the aforementioned changes, taking some substance from primarily non-functional final sound(s) of the historical Nom Sg. The meaning of the notion of astmevaheldus ‘gradation’, on the other hand, seems to be subject to constant restriction in modern Estonian linguistics in order not to exceed the scope of its quantitative and distributive historical properties. However its new functional burden, which consists in distinguishing between certain grammatical meanings like Gen Sg (for example lõpu ‘of the end’) and Part Sg (for example lõppu ‘the end’), and its substantial manifestations based primarily on quantitative distinctions (for example /p/ vs. /pp/) makes it equivalent to certain phenomena which are not classed as gradation from the diachronic point of view (for example, historical gemination in short forms of Illat Sg, such as jõkke ‘to the river’). In the present paper I propose expanding the meaning of the notion of astmevaheldus ‘gradation’. Such expansion seems to be conditioned in contemporary Estonian by the substantial and functional homogeneity of phenomena which are and are not classed as astmevaheldus from the diachronic point of view. In the present approach astmevaheldus is a ternary opposition in Estonian.